La etapa formativa de Mario Vargas Llosa: reflexiones sobre la experiencia con el francés y la traducción de Rimbaud - Morales Mena, Javier Julián (Revista Letras UNMSM, 2022)
This article aims to shed light on a barely known aspect of Mario Vargas Llosa’s (Arequipa, Peru, 1936) trajectory: his work as a translator. It analyzes his translation of Arthur Rimbaud’s short novel Un coeur sous une soutane / Un corazón bajo la sotana (1989). Even though scholars and critics recognize the relevance of translation in Vargas Llosa’s intellectual formation, the set of events that could explain the authors’ interest and preference for French language and culture has been overlooked: Vargas Llosa’s encounter with Cesar Moro and his critical reflections about his work, altogether with his initiatory experience in Paris. Although scholars recognize translation as part of the formative process of the Nobel Prize in Literature, they do not pay much attention to a series of events that will guide their interest and preference for the French language and culture in its formative stage.To illustrate the relevance of translation in Vargas Llosa’s work, this essay aims to reconstruct the most substantial moments when the author realizes the significance of French language and culture for his literary formation. For this purpose, it analyzes the author’s statements in "The Corrupter”, the prologue to his translation of Rimbaud’s text.